Learning to Be Streetwise: The Acquisition of Accurate Judgments of Aggression. Issue 3 (4th May 2017) - Satchell, Liam; Akehurst, Lucy; Morris, Paul
Abstract : The detection of potential danger is an important factor in avoiding harm that is even more important for vulnerable populations such as children. This study explores whether children can recognise the potential for a dangerous encounter from observing the gait of an approaching individual. The participants are divided into three age groups: 13- to 15-year-olds, 16- to 17-year-olds, and over 18s. Participants made judgments of nine, point light presentations of people walking on a treadmill. Ratings of intimidation made by participants were used to assess their ability to detect the walkers' trait aggression. The ability to detect trait aggression accurately was found to increase with age, as does the consistency in ratings between individuals within the same age group. The importance of experiential learning in the acquisition of aggression detection skills is highlighted.